2016
DOI: 10.5194/acp-16-4511-2016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular transformations of phenolic SOA during photochemical aging in the aqueous phase: competition among oligomerization, functionalization, and fragmentation

Abstract: Organic aerosol is formed and transformed in atmospheric aqueous phases (e.g., cloud and fog droplets and deliquesced airborne particles containing small amounts of water) through a multitude of chemical reactions. Understanding these reactions is important for a predictive understanding of atmospheric aging of aerosols and their impacts on climate, air quality, and human health. In this study, we investigate the chemical evolution of aqueous secondary organic aerosol (aqSOA) formed during reactions of phenoli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
122
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(156 citation statements)
references
References 47 publications
23
122
0
Order By: Relevance
“…Biogenic volatile organic compounds could be transported from the low elevation regions in subtropical India and biogenic secondary organic aerosol has been found to be an important source in the Himalayas (Stone et al, 2012). A number of other previously reported monoterpene oxidation product formulas were also observed in our study (Table 3) (Claeys et al, 2007;Kleindienst et al, 2007;H. Zhang et al, 2018).…”
Section: Cho Compoundssupporting
confidence: 79%
See 1 more Smart Citation
“…Biogenic volatile organic compounds could be transported from the low elevation regions in subtropical India and biogenic secondary organic aerosol has been found to be an important source in the Himalayas (Stone et al, 2012). A number of other previously reported monoterpene oxidation product formulas were also observed in our study (Table 3) (Claeys et al, 2007;Kleindienst et al, 2007;H. Zhang et al, 2018).…”
Section: Cho Compoundssupporting
confidence: 79%
“…Although organic nitrate is not favored to be ionized in positive ESI-MS (Wan and Yu, 2006), organic nitrate formed from BVOC could be highly functionalized (Lee et al, 2016) and ionized in positive MS through other alkaline functional groups. Recent studies have shown that BVOCs, including isoprene (C 5 H 8 ) and monoterpenes (C 10 H 16 ), dominate the organic nitrate formation in the southeastern United States under the condition of the mixed anthropogenic NO x and BVOCs (Xu et al, 2014;Lee et al, 2016;H. Zhang et al, 2018).…”
Section: Chon Compoundsmentioning
confidence: 99%
“…These low‐volatility products will remain in the particle phase as SOA after droplet evaporation. Photochemical aging of phenolic compounds results in multiple generations of aqueous SOA products with a wide range of volatilities and chemical composition and is a likely source of highly oxidized organic molecules [ Yu et al ., ]. The importance of aqueous‐phase oxidation depends on how organic mass is distributed among compounds that have a range of Henry's law constants, reaction rates and SOA yields, and the abundance of condensed phase water.…”
Section: Biomass Burningmentioning
confidence: 99%
“…Aqueousphase methylglyoxal reaction products are expected to remain largely in the aerosol phase upon cloud droplet evaporation (Heaton et al, 2009;Loeffler et al, 2006). Syringol (2,6-dimethoxyphenol) and guaiacol (2-methoxyphenol) are also emitted in significant quantities from biomass burning, and previous studies have examined the bulk aqueous-phase photooxidation of syringol and guaiacol (Yu et al, 2014(Yu et al, , 2016, showing production of several CHO compounds that were also observed in the wildfire-influenced cloud water studied here (Table 3). Notably, aqueous SOA formation from phenolic compounds has been shown to enhance light absorption in the UV-visible region (Yu et al, 2014), suggesting that these brown carbon compounds in the cloud water may be important upon cloud droplet evaporation.…”
Section: Canadian Wildfire Influencementioning
confidence: 99%
“…In addition, observations of likely dinitroaromatics during all air mass influences, potentially from aqueous nitration of nitroaromatic compounds, have important implications because of their light-absorbing and mutagenic properties (Purohit and Basu, 2000;Zhang et al, 2011Zhang et al, , 2013. During wildfire influence, the cloud water showed evidence of aqueous SOA formation, including oligomer formation involving methylglyoxal Yasmeen et al, 2010) and aqueousphase reactions of syringol and guaiacol (Yu et al, 2014(Yu et al, , 2016. Monoterpene-derived organosulfates and organonitrates (Surratt et al, 2008) were observed in the cloud water during all air mass influences, similar to previous cloud water studies (Boone et al, 2015;Pratt et al, 2013).…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%